Triple bonds between iron and heavier group-14 elements in the AFe(CO)3− complexes (A = Ge, Sn, and Pb). Issue 40 (25th April 2019) - Wang, Jia-Qi; Chi, Chaoxian; Lu, Jun-Bo; Meng, Luyan; Luo, Mingbiao; Hu, Han-Shi; Zhou, Mingfei; Li, Jun
Abstract : Heteronuclear transition-metal-main-group element carbonyl anion complexes of AFe(CO)3 − (A = Ge, Sn, and Pb) are prepared using a laser vaporization supersonic ion source in the gas phase, which were studied by mass-selected infrared (IR) photodissociation spectroscopy. Abstract : Heteronuclear transition-metal-main-group element carbonyl anion complexes of AFe(CO)3 − (A = Ge, Sn, and Pb) are prepared using a laser vaporization supersonic ion source in the gas phase, which were studied by mass-selected infrared (IR) photodissociation spectroscopy. The geometric and electronic structures of the experimentally observed species are identified by a comparison of the measured and calculated IR spectra. These anion complexes have a 2 A1 doublet electronic ground state and feature an AFe triply bonded C 3v structure with all of the carbonyl ligands bonded at the iron center. Bonding analyses of AFe(CO)3 − (A = C, Si, Ge, Sn, Pb, and Fl) indicate that the complexes are triply bonded between the valence n p atomic orbitals of bare group-14 atoms and the hybridized 3d and 4p atomic orbitals of iron.